Acerca da natureza e do caráter epistêmico das intuições - Nitsche, Roberto Schmitz (2024)
This thesis investigates two fundamental inquiries: the nature of intuitions and their reliability as an epistemic source. In the first section, we will explore the main approaches to the nature of intuitions, beginning with the debate on whether they are homogeneous or heterogeneous mental states. A new perspective will be proposed that recognizes heterogeneity in one aspect and homogeneity in another, allowing a more comprehensive understanding that facilitates the development of a general theory. Next, we will examine two reductionist approaches: the first regards intuitions as beliefs, while the second conceives them as dispositions or inclinations to form beliefs. Contrasting these views, a non-reductionist approach will be presented, asserting that intuitions are a unique type of mental state, arguing that it provides a more solid foundation for comprehending the nature of intuitions. In the following chapter, reasons opposing the development of a general theory on the nature of intuitions will be discussed and rejected. In the last chapter of the first section, a new proposal regarding the nature of intuitions will be presented, which can be integrated into the non-reductionist approach. This proposal will explain why there is an irresolvable conflict between the presented approaches. In the second section, we will investigate whether intuitions are reliable for guiding us to knowledge. The first chapter will consist of the presentation of one of the main contemporary challenges against the reliability of intuitions, where we will examine how experimental philosophers seek to demonstrate that intuitions are prone to various biases. The subsequent chapter will address the main concerns related to the methodology and results achieved by such experimental studies. The two following chapters will be dedicated to attempts to defend the reliability of intuitions. In the first one, we will analyze the possibility of calibrating intuitions, with the aim of generating improvements in this epistemic source to overcome reliability issues. Following that, we will investigate the idea of using only the intuitions of experts, rather than the general intuitions of people. In the last chapter, we will critically explore an approach that contends that philosophy does not rely on intuitions.